Aeroelastic tailoring of oscillating supersonic wing with external stores - Abdullah, Nur Azam; Sulaeman, Erwin (Trans Tech Publications Ltd., Switzerland, 2014)
This paper presents aeroelastic tailoring optimization of a swept back supersonic wing with external stores using composite structure material for the wing skin. The analysis has been conducted to calculate the flutter speeds at several altitudes ranging from a negative altitude of -7,943 ft until 30000 ft. MSC Nastran software is used to determine the flutter speed. The objective is to get the lowest possible wing weight by varying the wing skin composite fly angle and thickness as the optimization variables and by considering flutter speed as the optimization constraint. The constraint is imposed such that the flutter speed should be similar or higher than flutter speed of a previously investigated supersonic wing having similar planform but using aluminum as wing skin. The use of composite suggested that each composite layer thickness and fiber angle can be manipulated to achieve the target. The present results indicate that the weight of the composite wing skin can be reduced by 70 % compared to the aluminum wing skin while retaining similar or better flutter speed boundary envelope